Ultra-wide band and high efficient Polarization converting metasurface employing Bell-shaped unit cell for RCS reduction - Sukumar Vidhya; Madurakavi Karthikeyan (Results in Engineering)
Polarization is a dominant parameter regarding communication systems in recent times. The standard polarization techniques can be used only to a certain extent because of their huge size and limited bandwidth constraints. A design of bell-shaped polarization converting metasurface (PCMS) is presented in this paper which is highly efficient for Radar cross section (RCS reduction) and also operates in ultra-wideband. The designed PCMS attains a polarization conversion ratio of >90 % by demonstrating the transformation of the linear polarization wave to its orthogonal counterpart. The PCMS is arranged in a triangular chessboard configuration to reduce the RCS. RCS reduction is obtained by achieving destructive interference, accomplished by two unit cells. The two unit cells, PCMS and its mirror will have a phase difference of 180 ± 37° The phase cancellation is obtained by rotating and arranging the proposed PCMS at 90°, 180° and 270° RCS reduction is obtained in a frequency range from 4 GHz to 24.8 GHz with 144 % FBW. This PCMS is verified experimentally. A good agreement is found between the simulation and the experimental results.